2022
DOI: 10.3389/fcimb.2022.943407
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Is Associated With Shorter Time to Target Cycle Threshold Value in Patients With SARS-CoV-2 Omicron Variant

Abstract: BackgroundLimited data are available on the responses to vaccination for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant in the Chinese population. This study aimed to investigate whether vaccination could alter the disease course of SARS-CoV-2 Omicron variant.MethodsA retrospective cohort included 142 patients who had no or mild symptoms and were admitted to our department for centralized isolation after being locally infected with SARS-CoV-2 Omicron variant from March 4 to 30, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…This protection waned significantly after 6 months. However, Wu et al [ 10 ] found that a three-dose booster vaccination did not attenuate the target Ct value compared with a two-dose primary vaccination. Munro et al [ 34 ] conducted a multicenter, blinded, phase 2, randomized controlled trial to investigate the effectiveness of four-dose boosters against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protection waned significantly after 6 months. However, Wu et al [ 10 ] found that a three-dose booster vaccination did not attenuate the target Ct value compared with a two-dose primary vaccination. Munro et al [ 34 ] conducted a multicenter, blinded, phase 2, randomized controlled trial to investigate the effectiveness of four-dose boosters against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports on risk factors that influence the persistence of SARS-CoV-2 RNA shedding [ [7] , [8] , [9] ]. In a recent study of 142 patients with SARS-CoV-2 Omicron variant infection from March 4 to 30, 2022 in China, vaccination was found to be a protective factor against shorter viral shedding time in these patients [ 10 ]. Herein, the effect of SARS-CoV-2 vaccines on viral clearance time was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Nghiên cứu của chúng tôi cũng thấy rằng giá trị CT giữa 2 nhóm tiêm và không tiêm vắc-xin cũng không có sự khác biệt. Khác với chúng tôi, nghiên cứu của tác giả Wu và cộng sự trên 142 người bệnh COVID-19 cho thấy nhóm tiêm vắc-xin chỉ mất trung bình 12.6 ngày để đạt mức CT≥35, so với 14.8 ngày ở nhóm không tiêm vắc-xin [10]. Sự khác biệt này liên quan đến sự khác nhau về thời điểm khảo sát, do nguồn lực y tế giới hạn nên chúng tôi chỉ có thể đánh giá CT-PCR vào 1 thời điểm ngày 7 sau theo dõi, điều trị.…”
Section: Bàn Luậnunclassified
“…Earlier clinical studies on wild strains of SARS-CoV-2 showed that laboratory indicators of infection, such as lymphocyte count, T lymphocyte count, liver enzyme index, myocardial enzyme index, and D-dimer, are useful for predicting whether patients develop severe disease [ 9 , 10 ]. The Omicron variant strain has been reported to have a shorter incubation period, higher infectivity, and pathogenicity and to produce a higher viral load than the original strain [ 11 ]. The local outbreak in Shanghai occurred after widespread vaccination of the population against COVID-19.…”
Section: Introductionmentioning
confidence: 99%